The Influence of Local Habitat and Microclimate on the Levels of Secondary Metabolites in Slovak Bilberry (Vaccinium myrtillus L.) Fruits - Zuzana Vaneková (Plants, 2020)
The berries of Vaccinium myrtillus L. are usually collected in the wild for the purpose of being a food source. They are naturally high in phenolic compounds, which possess antioxidative properties, so the berries are therefore often labeled as “functional foods”. This study evaluated seven samples of bilberry fruits from different locations in Slovakia for the content of the main phenolic compounds (anthocyanins, flavonoids and tannins) using European Pharmacopoeia 9 spectrophotometric methods. A thorough analysis of environmental factors showed that several phenolic constituents are closely corresponding with their respective environments, as well as with each other. The environmental factors with statistically significant correlations in this study are altitude, habitat type, sunlight exposure, and soil carbon content. Our findings suggest that the berries collected at sunny sites with no topsoil damage contain more phenolic compounds. The lowest amounts of phenolic compounds were found in samples from dense forests or with visible soil erosion and windthrow damage. The negative effect of windthrow damage on the levels of secondary metabolites in bilberry fruits has been described for the first time. This study observed no relationship between the amount of phenolic compounds and soil pH, soil nitrogen levels, or slope exposition.